2016
DOI: 10.5897/ajar2016.10833
|View full text |Cite
|
Sign up to set email alerts
|

Propolis extract coated in Pera orange fruits: An alternative to cold storage

Abstract: Orange (Citrus sinensis) is a non-climacteric fruit that can be stored for long periods. However, the development of physiological and phytopathological disorders limits its postharvest storage. The objective of this study was to evaluate the effects of coating orange with propolis extract on the physicochemical characteristics of the "Pera" orange during storage under ambient temperature. The fruits were selected and submitted to five postharvest treatments, three different forms of dip coating (70% alcohol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The present work showed that the increase in TSS in chillies treated with propolis was significantly delayed as compared to control (p < 0.05), which suggested a slower conversion of starch into watersoluble sugars (Samira et al, 2013). This observation was in conformity to previous studies reporting on a lower TSS values of other fruits treated with propolis, such as bananas (Passos et al, 2016) and peppers (Ekhuemelo et al, 2018). A slower increase in TSS in propolis-treated chillies in the present work thus indicated the potential of stingless bee propolis in delaying their ripening.…”
Section: The Effect Of 10% Propolis Aqueous Extract On Chemical Quali...supporting
confidence: 91%
See 1 more Smart Citation
“…The present work showed that the increase in TSS in chillies treated with propolis was significantly delayed as compared to control (p < 0.05), which suggested a slower conversion of starch into watersoluble sugars (Samira et al, 2013). This observation was in conformity to previous studies reporting on a lower TSS values of other fruits treated with propolis, such as bananas (Passos et al, 2016) and peppers (Ekhuemelo et al, 2018). A slower increase in TSS in propolis-treated chillies in the present work thus indicated the potential of stingless bee propolis in delaying their ripening.…”
Section: The Effect Of 10% Propolis Aqueous Extract On Chemical Quali...supporting
confidence: 91%
“…Previous studies have reported similar observations on the effectiveness of honeybee propolis to delay weight loss of dragon fruits and cherry tomatoes (Zahid et al, 2013;Pobiega et al 2020). Propolis was also found to delay the reduction of weight in many fruits including bananas, grapefruits, grapes, mangoes, oranges, papayas, pomegranates, bell peppers, and tomatoes (Passos et al, 2016). This, therefore, suggested the effectiveness of propolis extract in creating a protective layer on the chillies which reduced the loss of moisture, thus lowering the rate of weight loss.…”
Section: The Effect Of 10% Propolis Aqueous Extract On Physical Quali...supporting
confidence: 65%
“…3). Flavia et al (2016) also reported delayed weight loss in propolis extract coated pera orange fruits at ambient conditions.…”
Section: Fig 2 Change In Firmness Of Banana Due To Treatments With mentioning
confidence: 87%
“…Also, through the storage for 25 days, both the control and 2.5% propolis exhibited raise in the TA content. Mendes et al (26) found that the impact was significantly more obvious in the postharvest control sample. The exhaustion of organic acids during respiration could be explained as the reduction of TA in the fruit (32).…”
Section: Figure 5 Effect Of (A) Propolis and Aloe Vera Levels And (B)...mentioning
confidence: 95%